Using wordclouds to define an innovative business model for HVAC industry in buildings in the tertiary sector (2017)
This study identifies the main characteristics of the standard business models of the HVAC (Heating, Ventilation and Air Conditioning) sector worldwide, specifically those whose value proposition is related to the supply, commercialization and sale of weatherization services through the use of clean and efficient technologies. All of the above in order to define a proposal for an innovative business model adapted to the Colombian context that contributes to the construction of projections at the scales of consumption of air conditioning with their respective implications for energy and tariff consumption. This research was conceived Inquiring in business and scientific databases, field work and other secondary sources.